Comparative genomic analysis of four multidrug-resistant isolates of Acinetobacter baumannii from Georgia. (June 2020) - Farlow, Jason; Nozadze, Maia; Mitaishvili, Nino; Kotorashvili, Adam; Kotoria, Nato; Arobelidze, Keto; Tavadze, Viktoria; Simsive, Tsiuri; Imnadze, Paata; Latif, Nabil; Nikolich, Mikeljon P.; Washington, Michael; et al.
Highlights: Genomes of four multidrug-resistant (MDR) Georgian Acinetobacter baumannii isolates were sequenced. Multi-locus sequence typing was performed on strains 0830, 0365, 4022, and 2846. In silico analyses resolved antibiotic resistance gene content and clonal relatedness. The data represent the first clonal subtypes and genomes for Georgian MDR Acinetobacter baumannii . Abstract: Objectives: This study reports the draft genomes of four newly isolated multidrug-resistant (MDR) Acinetobacter baumannii ( A. baumannii ) isolates (0830, 0365, 4022, and 2846) from western Georgia to identify putative antimicrobial resistance genes (ARGs) and to determine the clonal subtypes of local clinical isolates. Methods: An Illumina MiSeq sequencer was used to perform whole-genome sequencing (WGS). The Vitek 2 automated system was used for microbial identification and antimicrobial resistance profiling. Results: Taxonomical identification as A. baumannii was confirmed by WGS. In silico analyses resolved their ARG content and clonal relatedness using the Oxford (Oxf) and Pasteur (Pas) multi-locus sequence typing schemes. Isolates 0365 and 4022 displayed similar allelic profiles corresponding to ST944Oxf/ST78Pas. Isolate 2846 displayed a different allelic profile consistent with ST19Pas/IC 1 (International or European Clone I) and exhibited a novel Oxford ST that was designated as 1868. Isolate 0830 displayed the ST78Pas allelic profile, similar to isolates 0365 and 4022, and also possessed a single allelic mismatch in the gpi gene, resulting in an ST1104Oxf allele profile in the Oxford typing scheme. Conclusion: Circulating MDR A. baumannii exhibited genetic heterogeneity with variations in the structure and content of genomic A. baumannii resistance islands and encoded multiple putative ARGs. This report represents the first clonal subtype information and genomic characterization of MDR A. baumannii in Georgia and may inform future epidemiological investigations.